2016
DOI: 10.1371/journal.pone.0149125
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP) and Cyclic ADP-Ribose (cADPR) Mediate Ca2+ Signaling in Cardiac Hypertrophy Induced by β-Adrenergic Stimulation

Abstract: Ca2+ signaling plays a fundamental role in cardiac hypertrophic remodeling, but the underlying mechanisms remain poorly understood. We investigated the role of Ca2+-mobilizing second messengers, NAADP and cADPR, in the cardiac hypertrophy induced by β-adrenergic stimulation by isoproterenol. Isoproterenol induced an initial Ca2+ transients followed by sustained Ca2+ rises. Inhibition of the cADPR pathway with 8-Br-cADPR abolished only the sustained Ca2+ increase, whereas inhibition of the NAADP pathway with ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 45 publications
5
39
0
Order By: Relevance
“…Although CD38 is known to be a responsible enzyme for both cADPR and NAADP synthesis in vitro and in some cells [12, 34], it is not likely the case in skeletal muscle cell. These findings are consistent with our previous research that CD38 mediates only cADPR formation in cardiomyocytes in response to ISO treatment [11]. Moreover, NAADP was prerequisite for cADPR formation in ISO- treated cardiomyocytes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although CD38 is known to be a responsible enzyme for both cADPR and NAADP synthesis in vitro and in some cells [12, 34], it is not likely the case in skeletal muscle cell. These findings are consistent with our previous research that CD38 mediates only cADPR formation in cardiomyocytes in response to ISO treatment [11]. Moreover, NAADP was prerequisite for cADPR formation in ISO- treated cardiomyocytes.…”
Section: Discussionsupporting
confidence: 93%
“…2A & B). Consistent with these findings, CD38 has been shown to be responsible for ISO-induced cADPR production, but not NAADP production in cardiomyocytes [11]. We further examined cADPR formation in the muscle fibers from both groups under electrical stimuli (ES) and/ or ISO treatment.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with our result, Uh‐Hyun Kim et al . reported that CD38 KO mice were protected from the ISO‐mediated cardiac hypertrophy via Ca 2+ signalling pathway . As we expected, the active NFATc4 expression was significantly decreased in CD38 knockdown cells, suggesting that CD38 deficiency was sufficient to reverse Ang‐II‐induced the activation of the calcineurin–NFATc4 pathway.…”
Section: Discussionsupporting
confidence: 70%
“…In the case of noncompetitive inhibition, increasing the amount of substrate does not affect the level of inhibition. This difference may be important in considering the optimal inhibitor of CD38, since CD38 catalyzes reactions that lead to a wide range of second messengers, some of which are potent calcium (Ca 21 ) mobilizers (Lee, 2012;Gul et al, 2016). It remains possible that increased production of these second messengers contributes to ischemia-induced Ca 21 overload in myocytes (Zimmerman and Hülsmann, 1966;Hausenloy and Yellon, 2013).…”
Section: Discussionmentioning
confidence: 99%